2016
DOI: 10.1007/s13205-015-0342-1
|View full text |Cite
|
Sign up to set email alerts
|

Metals-induced functional stress in sulphate-reducing thermophiles

Abstract: All toxic metals have been known to inhibit different activities of sulphate-reducing bacteria (SRB) at different concentrations. The present study delineates functional responses of two thermophilic SRB species (Desulfotomaculum reducens-HA1 and Desulfotomaculum hydrothermale-HA2) to toxic metals. Bacterial activity was assessed in terms of sulphate reduction and metal precipitation employing four concentrations (1, 5, 10 and 15 ppm) of three dissolved toxic metals (Cu, Cr and Ni) independently. Both sulphido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…SRB make morphologically and physiologically a diverse group of obligatory anaerobes which share the ability to dissimilate sulfate to sulfide while oxidizing various growth substrates (Willis et al 1997 ). These prokaryotic microorganisms are much versatile in their metabolism as well as in the environmental conditions in which they thrive and particularly make their importance in specific ecosystems such as acid mine drainages, cyanobacterial microbial mats, deep-sea hydrothermal vents, hypersaline microbial mats, marine and freshwater sediments, methane zone of marine sediments, oil fields’ environments, polluted environments such as anaerobic purification plants, rhizosphere of plants and rice fields (Fauque 1995 ; Dhillon et al 2003 ; Rabus et al 2006 ; Foti et al 2007 ; Leloup et al 2007 ; Ollivier et al 2007 ; Muyzer and Stams 2008 ; Hussain and Qazi 2016 ; Wissuwa et al 2016 ). In the above mentioned ecosystems, SRB have to cope with drastic physicochemical conditions including high temperature and high pressure, etc.…”
Section: Ecology and Biotechnology Of Srbmentioning
confidence: 99%
See 3 more Smart Citations
“…SRB make morphologically and physiologically a diverse group of obligatory anaerobes which share the ability to dissimilate sulfate to sulfide while oxidizing various growth substrates (Willis et al 1997 ). These prokaryotic microorganisms are much versatile in their metabolism as well as in the environmental conditions in which they thrive and particularly make their importance in specific ecosystems such as acid mine drainages, cyanobacterial microbial mats, deep-sea hydrothermal vents, hypersaline microbial mats, marine and freshwater sediments, methane zone of marine sediments, oil fields’ environments, polluted environments such as anaerobic purification plants, rhizosphere of plants and rice fields (Fauque 1995 ; Dhillon et al 2003 ; Rabus et al 2006 ; Foti et al 2007 ; Leloup et al 2007 ; Ollivier et al 2007 ; Muyzer and Stams 2008 ; Hussain and Qazi 2016 ; Wissuwa et al 2016 ). In the above mentioned ecosystems, SRB have to cope with drastic physicochemical conditions including high temperature and high pressure, etc.…”
Section: Ecology and Biotechnology Of Srbmentioning
confidence: 99%
“…A number of studies, based on the applications of SRB have been carried out for the treatment of simulated and real wastewaters contaminated with a range of pollutants. The latest advancement in the applications of SRB have shown that SRB are used to treat various environmental contaminants including metals (Hussain and Qazi 2016 ; Mothe et al 2016 ; Zhang et al 2016b ), metalloids (Battaglia-Brunet et al 2012 ; Altun et al 2014 ; Sahinkaya et al 2015 ) sulfates (Hussain and Qazi 2014 , 2016 ; Hussain et al 2014a ), methane (Krukenberg et al 2016 ), various non-methane hydrocarbons e.g. alkanes (Callaghan et al 2012 ; Khelifi et al 2014 ; Kleindienst et al 2014 ; Herath et al 2016 ) and alkenes (Fullerton et al 2013 ), alicyclic hydrocarbons e.g.…”
Section: Applications Of Srbmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that this method is expensive and can possibly create generation of secondary pollutants, its application can be problematic (Ihsanullah et al 2016 ). Owing to high efficacy and low operational cost, the bioremedial strategies have been advocated, including studies based on the utilization of genetic potential of microorganisms, originally isolated from the contaminated environment (Thacker et al 2006 ; Cetin et al 2008 ; Martins et al 2010 ; Hussain and Qazi 2016 ). The line of action has high likelihood of isolating microbial cultures which can successfully be augmented for remediating the contamination.…”
Section: Introductionmentioning
confidence: 99%